Critical properties of the susceptible-exposed-infected model on a square lattice. (29th April 2015) - Wada, Alexander H O; Tomé, Tânia; de Oliveira, Mário J
Abstract: The critical properties of the stochastic susceptible-exposed-infected model on a square lattice is studied by numerical simulations and by the use of scaling relations. In the presence of an infected individual, a susceptible becomes either infected or exposed. Once infected or exposed, the individual remains forever in this state. The stationary properties are shown to be the same as those of isotropic percolation so that the critical behavior puts the model into the universality class of dynamic percolation.